A Generalised Energy-Efficient Time-Based Communication Protocol for Wireless Sensor Networks. (22nd July 2009) - AL-khdour, Tayseer; Baroudi, Uthman
To increase network lifetime, and reduce energy consumption of a WSN, this paper proposes a Generalised Energy-Efficient Time-Based Communication Protocol (GET). GET is a distributed approach that jointly optimises the routing tree and the medium access schedule for data transmissions. GET works in rounds, each round is composed of four phases, namely: selecting gateways, building a routing tree, establishing a TDMA schedule, and data transmission. GET is compared with EAD and LEACH via extensive simulation experiments. Simulation results show that our proposal can provide significant improvement in terms of network lifetime, aggregate throughput, and energy consumption.